2015
DOI: 10.14814/phy2.12645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UGT2B17 gene deletion on the steroid profile of an athlete

Abstract: The measurement of the testosterone to epitestosterone ratio (T/E ratio) in urine is often used as a marker for testosterone administration in the doping control field. This study examines the frequencies of the different expression forms of the UGT2B17 gene, and assesses their effects on this marker in volunteer subjects. The sample for this descriptive study was composed of male and female athletes aged between 16 and 55 years old who practiced different sports disciplines. All participants underwent a sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…UGT2B17 polymorphisms also pose a significant challenge in detection of testosterone doping by athletes, where metabolite ratios are used to create individual biological passports. 26,27 Therefore, to test if the testosterone metabolite ratios are doseindependent, we quantified complete testosterone metabolite panel after treating with two oral doses (200 and 800 mg).…”
Section: Figurementioning
confidence: 99%
“…UGT2B17 polymorphisms also pose a significant challenge in detection of testosterone doping by athletes, where metabolite ratios are used to create individual biological passports. 26,27 Therefore, to test if the testosterone metabolite ratios are doseindependent, we quantified complete testosterone metabolite panel after treating with two oral doses (200 and 800 mg).…”
Section: Figurementioning
confidence: 99%
“…7,8 We have previously described the concordance between the UGT2B17 deletion polymorphism and the urinary excretion of testosterone. 9 Individuals devoid of the UGT2B17 gene display lower T/E ratios than those with 1 or 2 insertion polymorphism, 8,10 and after administration of testosterone these individuals rarely reach a T/E ratio above 4. [11][12][13] It is known that transdermal administration of T gel causes an increase in serum T and dihydrotestosterone (DHT), markers that have been suggested for longitudinal monitoring in a blood steroid profile.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the concordance between the UGT2B17 deletion polymorphism and the urinary excretion of testosterone . Individuals devoid of the UGT2B17 gene display lower T/E ratios than those with 1 or 2 insertion polymorphism, and after administration of testosterone these individuals rarely reach a T/E ratio above 4 …”
Section: Introductionmentioning
confidence: 99%
“…Here, however, the authors concluded that if the genotype ( del / del ) would have been a known parameter and factored in, the monitored profile would also have been considered suspicious. Due to its critical role, the addition of the athletes’ UGT2B17 genotype has been suggested to be implemented into the ABP also by other groups studying the impact of the gene deletion on steroid profile analysis …”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Due to its critical role, the addition of the athletes' UGT2B17 genotype has been suggested to be implemented into the ABP also by other groups studying the impact of the gene deletion on steroid profile analysis. [76] Alternative to the monovariate adaptive model currently employed in the ABP, Alladio et al investigated potential advantages of multivariate statistical approaches, utilizing the same urinary steroids commonly monitored in routine doping controls. [77] In a proof-of-concept study using principal component analysis (PCA) and Hotelling T [2] test, the principle applicability of the strategy was successfully demonstrated.…”
Section: Steroid Profilingmentioning
confidence: 99%